Efficacy and safety of standard of care with/without bevacizumab for platinum‐resistant ovarian/fallopian tube/peritoneal cancer previously treated with bevacizumab: The Japanese Gynecologic Oncology Group study JGOG3023. Issue 1 (18th November 2021) - Shoji, Tadahiro; Enomoto, Takayuki; Abe, Masakazu; Okamoto, Aikou; Nagasawa, Takayuki; Oishi, Tetsuro; Nagase, Satoru; Mori, Masahiko; Inokuchi, Yuki; Kamiura, Shoji; Komiyama, Shinichi; Takeshima, Nobuhiro; et al.
Abstract: We investigated the efficacy and safety of further bevacizumab therapy in patients with platinum‐resistant ovarian cancer whose disease had progressed after bevacizumab plus chemotherapy. In this multicenter, open‐label, phase II trial (JGOG3023), patients were randomized 1:1 to a single‐agent chemotherapy alone (either pegylated liposomal doxorubicin [40 or 50 mg/m 2 administered intravenously], topotecan [1.25 mg/m 2 intravenously], paclitaxel [80 mg/m 2 intravenously], or gemcitabine [1000 mg/m 2 intravenously]) or single‐agent chemotherapy + bevacizumab (15 mg/m 2 intravenously). The primary endpoint was investigator‐assessed progression‐free survival (PFS) according to RECIST version 1.1. Secondary endpoints were overall survival (OS), objective response rate (ORR), and response rate according to Gynecological Cancer Intergroup cancer antigen 125 criteria. In total, 103 patients were allocated to chemotherapy (n = 51) or chemotherapy + bevacizumab (n = 52). Median investigator‐assessed PFS was 3.1 and 4.0 mo in each group, respectively (hazard ratio [HR] = 0.54, 95% confidence interval [CI]: 0.32‐0.90, P  = .0082). Median OS was 11.3 and 15.3 mo in each group, respectively (HR = 0.67, 95% CI: 0.38‐1.17, P  = .1556). Respective ORRs were 13.7% and 25.0% ( P  = .0599) and response rates were 16.7% and 21.4% ( P  = .8273). The incidence of grade ≥3 treatment‐related AEs was 42.0% in the chemotherapy group and 54.9% in the chemotherapy + bevacizumab group; AEs were well tolerated, with only 2 and 12 events leading to discontinuation of therapy, respectively. Bevacizumab was effective beyond progressive disease and AEs were manageable. The observed improvement in PFS requires further verification. Abstract : We evaluated chemotherapy ± bevacizumab for platinum‐resistant recurrent ovarian cancer previously treated with bevacizumab. The results of this phase II study demonstrate the efficacy and manageable toxicity of continuing bevacizumab beyond progressive disease in patients with platinum‐resistant recurrent ovarian cancer previously treated with bevacizumab for front‐line or platinum‐sensitive recurrent ovarian cancer.